Influence of the β−phase content and degree of crystallinity on the piezo- and ferroelectric properties of poly (vinylidene fluoride) - Gomes, J. (2010)
The ferroelectric switching behaviour and piezoelectric response of poly(vinylidene fluoride) (PVDF) prepared by drawing at stretching ratios from 1 to 5 and temperatures from 80 to 140 ºC has been studied. Stretching ratio and temperature deeply influences the α (non ferroelectric) to β (ferroelectric) phase transformation. The variations in the phase content are accompanied by changes in the degree of crystallinity and the microstructure, all of them influencing the macroscopic piezoelectric and ferroelectric response of the material. This work shows how the piezo- and ferroelectric behaviour of PVDF depend on the aforementioned parameters and, in particular, on the crystalline β-phase content. Coercive electric field, remnant polarization and saturation polarization increase with increasing ferroelectric β-phase content in the sample. In a similar way, samples with higher β-phase content show higher d33 piezoelectric coefficients.